The Impact of Structural Reforms on Poverty : A Simple Methodology with Extensions - McCulloch, Neil (World Bank, Washington, DC, 2014)
Structural reforms are often designed to change the prices of key goods and services. Since the overall intention of such reforms is the reduction of poverty, it is important to understand how the resulting price changes affect the poor. However, organizations seeking to provide timely advice to policymakers in developing countries often do not have the data and resources needed to undertake the most sophisticated approaches to such analysis. McCulloch outlines a simple methodology based on the analysis of household survey data to estimate the first-order impact of a variety of structural reforms. He also elaborates on the ways in which this methodology may be extended in a flexible way to account for particular features of a country in question. Finally, he outlines the direction of some extensions on the approach to tackle dynamics, risk, and qualitative poverty analysis.